2004
DOI: 10.1128/jcm.42.9.4007-4015.2004
|View full text |Cite
|
Sign up to set email alerts
|

Phage Types and Genotypes of Shiga Toxin-Producing Escherichia coli O157:H7 Isolates from Humans and Animals in Spain: Identification and Characterization of Two Predominating Phage Types (PT2 and PT8)

Abstract: Phage typing and DNA macrorestriction fragment analysis by pulsed-field electrophoresis (PFGE) were used for the epidemiological subtyping of a collection of Shiga toxin-producing Escherichia coli (STEC) O157:H7 strains isolated in Spain between 1980 and 1999. Phage typing distinguished a total of 18 phage types among 171 strains isolated from different sources (67 humans, 82 bovines, 12 ovines, and 10 beef products). However, five phage types, phage type 2 (PT2; 42 strains), PT8 (33 strains), PT14 (14 strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 63 publications
(60 reference statements)
3
32
1
3
Order By: Relevance
“…None contained sfpA, which encodes fimbriae and is a defining characteristic of SF EHEC O157:NM (8). The 391 EHEC O157:H7 strains investigated belonged to 19 phage types (PTs) ( Table 1), which represent the spectrum of PTs within E. coli O157:H7 in Germany and are in concordance with other studies from Germany (1,13) and other European countries (14,20). The cdt-V-positive strains belonged to five different PTs (Table 1).…”
supporting
confidence: 73%
“…None contained sfpA, which encodes fimbriae and is a defining characteristic of SF EHEC O157:NM (8). The 391 EHEC O157:H7 strains investigated belonged to 19 phage types (PTs) ( Table 1), which represent the spectrum of PTs within E. coli O157:H7 in Germany and are in concordance with other studies from Germany (1,13) and other European countries (14,20). The cdt-V-positive strains belonged to five different PTs (Table 1).…”
supporting
confidence: 73%
“…The existence of a VTEC O157 subpopulation has also been supported by the observation that VTEC O157 strains isolated from cases of human disease usually belong to a nonrandom subset of PTs (15)(16)(17)(18)(19)(20). Although the phage types are related to the susceptibility of VTEC O157 to infection with a panel of phages and may not correlate with their virulence potentials, significant differences have been reported in the distribution of the PTs among VTEC O157 isolates from human and bovine sources by different authors (15)(16)(17)(18)(19)(20) and can thus be considered a good epidemiological marker for the purpose of identifying VTEC O157 subpopulations.…”
Section: Discussionmentioning
confidence: 74%
“…Although this technique was developed more than 2 decades ago, it still remains a useful approach to characterize VTEC O157 strains. Interestingly, it has been observed that while the isolates from cattle may span a wide portion of the entire PT panel (15), the strains isolated from both outbreaks and sporadic cases of human disease usually belong to a restricted number of PTs. In particular, VTEC O157 strains isolated from human infections in Europe mainly belong to PT8 and PT2 (15)(16)(17)(18), PT21/28 (19,20), and PT32 (16).…”
Section: Erocytotoxin (Vt)-producing Escherichia Coli (Vtec) O157mentioning
confidence: 99%
See 1 more Smart Citation
“…The phage typing have become the most commonly used and the only internationally standardized subtyping method for STEC O157 (Allison et al, 2000;Mora et al, 2004). Unfortunately, we were unable to type our strains during analyses due to the lack of phages.…”
Section: Discussionmentioning
confidence: 99%